PRAKTEK E-GOVERNMENT DALAM ADMINISTRASI KEPENDUDUKAN Studi Pelaksanaan Perekaman e-KTP di Kabupaten Pemalang - Esha Yanuar R; Puji Astuti; Rr Hermini (Journal of Politic and Government Studies, 2013)
ABSTRACTThis study was conducted to describe the implementation of programe in the “electronik Kartu Tanda Penduduk/e-KTP” (electronic civil ID card) in Pemalang regency. The program is motivated by the development of information and communication technologies are adopted into the system of governance in the form of e-government. Implementation of e-KTP is intended to manifest valid demographic data base. So that it can be support the implementation of good governance.To explain the research implementation of e-KTP, then used descriptive qualitative research methods. Subject and object in this study is the Department of Population and Civil Registration Pemalang, Head of Population Registration, Technical Supervisor District, operator services, and society in general. The method of data collection was through interviews and observations with the selection of purposive informants.The study says that the implementation of e-KTP recording in Pemalang can be said is not maximized. Many constraints make the implementation of this program to be blocked, such as a less effective socialization, inadequate recording facility and bad mobilization planning.Recommendations for future research, is needed good socialization, communication, coordination and cooperation between the government and the public, in order to unify the views in the policy implementation process. In addition, the use value of the e-KTP itself should really be utilized for the distribution of welfare of the people and to improve public access to all public services provided by the government.